Infrastructure Development and Its Socioeconomic Implications: A Study of Enrekang Regency - Nur Sandi Marsuni; Akmal Ridwan; Aisha R. Manou (Yayasan Amerta Insan Unggul, 2024)
This international collaborative research investigates the socioeconomic implications of rural infrastructure development in Enrekang Regency, Indonesia, through the partnership of researchers from Luxembourg, Seychelles, and the Maldives. Employing a qualitative descriptive design, the study gathered data via interviews, observations, and document analysis involving 18 participants, including local officials, community leaders, and residents. The findings reveal that improvements in road connectivity, health centers, and educational facilities in Janggurara Village have significantly enhanced accessibility, economic productivity, and social inclusion. Infrastructure upgrades stimulated agricultural trade, supported local enterprises, and improved access to education and healthcare, particularly benefiting women and elderly residents. However, governance challenges persist, including limited community participation, land acquisition disputes, and environmental disruptions. Comparative insights from Luxembourg underscore the role of governance efficiency and institutional frameworks, while lessons from Seychelles and the Maldives highlight the value of community-based and climate-resilient approaches. The study concludes that sustainable infrastructure development in rural Indonesia requires participatory governance, transparent decision-making, and climate-adaptive planning. Transnational collaboration enhances policy innovation by integrating diverse experiences and promoting mutual learning between developed and developing contexts. The research contributes to global discourse on rural transformation and supports the United Nations Sustainable Development Goals, particularly SDG 9 (Industry, Innovation, and Infrastructure) and SDG 11 (Sustainable Cities and Communities). Overall, this study demonstrates that inclusive, adaptive, and internationally informed infrastructure strategies are key drivers of equitable and resilient rural development.